Mapping places and people in a settler society: From discrepancy to good fit over one century of South African censuses - (:unkn) unknown (My University, 2012)
The dynamics of population and urbanization in South Africa have been recorded by a remarkable set of censuses during the 20th century. These censuses indicate a changing hierarchy of places that is typical of a settler society and of its representations of space and society. Over one century, the official census places and the pattern of population distribution have shifted from a selective colonial view of human settlements to an inclusive postcolonial society view closer to the distribution of the whole population.
Keywords: African Research